Activated Protein C Attenuates Severe Inflammation by Targeting VLA-3high Neutrophil Subpopulation in Mice - Sarangi, Pranita P; Lee, Hyun-Wook; Lerman, Yelena V; Trzeciak, Alissa; Harrower, Eric J; Rezaie, Alireza R; Kim, Minsoo (The Journal of immunology (1950), 2017)
The host injury involved in multiorgan system failure during severe inflammation is mediated, in part, by massive infiltration and sequestration of hyperactive neutrophils in the visceral organ. A recombinant form of human activated protein C (rhAPC) has shown cytoprotective and anti-inflammatory functions in some clinical and animal studies, but the direct mechanism is not fully understood. Recently, we reported that, during endotoxemia and severe polymicrobial peritonitis, integrin VLA-3 (CD49c/CD29) is specifically upregulated on hyperinflammatory neutrophils and that targeting the VLA-3high neutrophil subpopulation improved survival in mice. In this article, we report that rhAPC binds to human neutrophils via integrin VLA-3 (CD49c/CD29) with a higher affinity compared with other Arg-Gly-Asp binding integrins. Similarly, there is preferential binding of activated protein C (PC) to Gr1highCD11bhighVLA-3high cells isolated from the bone marrow of septic mice. Furthermore, specific binding of rhAPC to human neutrophils via VLA-3 was inhibited by an antagonistic peptide (LXY2). In addition, genetically modified mutant activated PC, with a high affinity for VLA-3, shows significantly improved binding to neutrophils compared with wild-type activated PC and significantly reduced neutrophil infiltration into the lungs of septic mice. These data indicate that variants of activated PC have a stronger affinity for integrin VLA-3, which reveals novel therapeutic possibilities.The host injury involved in multiorgan system failure during severe inflammation is mediated, in part, by massive infiltration and sequestration of hyperactive neutrophils in the visceral organ. A recombinant form of human activated protein C (rhAPC) has shown cytoprotective and anti-inflammatory functions in some clinical and animal studies, but the direct mechanism is not fully understood. Recently, we reported that, during endotoxemia and severe polymicrobial peritonitis, integrin VLA-3 (CD49c/CD29) is specifically upregulated on hyperinflammatory neutrophils and that targeting the VLA-3high neutrophil subpopulation improved survival in mice. In this article, we report that rhAPC binds to human neutrophils via integrin VLA-3 (CD49c/CD29) with a higher affinity compared with other Arg-Gly-Asp binding integrins. Similarly, there is preferential binding of activated protein C (PC) to Gr1highCD11bhighVLA-3high cells isolated from the bone marrow of septic mice. Furthermore, specific binding of rhAPC to human neutrophils via VLA-3 was inhibited by an antagonistic peptide (LXY2). In addition, genetically modified mutant activated PC, with a high affinity for VLA-3, shows significantly improved binding to neutrophils compared with wild-type activated PC and significantly reduced neutrophil infiltration into the lungs of septic mice. These data indicate that variants of activated PC have a stronger affinity for integrin VLA-3, which reveals novel therapeutic possibilities.